Deaths due to Fall From a Height in Adana - Eren, Ali; Arslan, Muhammet Mustafa; Hilal, Ahmet; Çekin, Necmi (The Bulletin of Legal Medicine, 2009)
This study was aimed to evaluate and discuss socio-demographic characteristics, frequency and origin of the deaths due to fall from a height in Adana. Records of Public Prosecutor Office and death certificates related 4010 forensic deaths, between 2003-2007, were investigated retrospectively and 315 deaths due to fall from a height taken in the scope of the study. Of all cases, 71.11% were male and the majority was between the 41-50 years. Overwhelming majority (81.59%) of cases were accidental falls while 14.92% had a suicidal origin. Furthermore, 36.50% of cases occurred in summer season. Places’ of falls were generally balcony, window and roof of apartments (house or workplace). Out of all cases only 12.38% underwent an autopsy procedure. In conclusion, considering deaths due to fall from a height, which are mostly secondary to preventable accidents, educational programs organized in order to increase the awareness of families, individuals from all age groups employers and additional safety measures to be taken will help a considerable decrease in such deaths.Key words: Fall from a height, death, accident, autopsy
Keywords: fall from a height; death; accident; autopsy